2004
DOI: 10.1590/s0036-36342004000500010
|View full text |Cite
|
Sign up to set email alerts
|

Enfermedad por meningococo, Neisseria meningitidis: perspectiva epidemiológica, clínica y preventiva

Abstract: Bacterial meningitis constitutes a significant global public health problem. In particular, Neisseria meningitidis continues to be a public health problem among human populations in both developed and developing countries. Meningococcal infection is present as an endemic and an epidemic disease. Meningococcal disease is manifested not only as meningitis, but also as meningococcemia. The latter is usually fulminant. The global persistence of N. meningitidis is due to the significant number of carriers and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
1
6
0
2
Order By: Relevance
“…The data presented in this, long, active-surveillance-based study, confirm that, contrary to what has been reported in one publication in Mexico, 5 N. meningitidis is the leading cause of BM in Tijuana, Mexico, with serogroup C being the most prevalent. This study, along with an active-surveillance publication from nine hospitals in Mexico, and an outbreak of meningococcal BM caused by serogroup C, with clonal complex ST-11 (mortality >35%) in Tijuana during 2013, 20,21 confirmed that meningococcal disease is endemic in the region, and universal vaccination should be seriously considered.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The data presented in this, long, active-surveillance-based study, confirm that, contrary to what has been reported in one publication in Mexico, 5 N. meningitidis is the leading cause of BM in Tijuana, Mexico, with serogroup C being the most prevalent. This study, along with an active-surveillance publication from nine hospitals in Mexico, and an outbreak of meningococcal BM caused by serogroup C, with clonal complex ST-11 (mortality >35%) in Tijuana during 2013, 20,21 confirmed that meningococcal disease is endemic in the region, and universal vaccination should be seriously considered.…”
Section: Discussionsupporting
confidence: 79%
“…In Mexico, based on previous published data, BM due to Neisseria meningitidis is considered to be a rare condition, with a total number of cases in the whole country as low as two per year. 5…”
Section: Introductionmentioning
confidence: 99%
“…The low carriage rates found in our study and those reported in Mexico are consistent with the low disease incidence rate reported in these two countries. Currently the burden of meningococcal disease in Mexico is low, with total national cases as low as two per year [73,74]. The prevalence of N. meningitidis carriage in healthy children and adolescents aged 10–19 years in Chile was reported to be 6.5% [75], and slightly lower in university students ages 18–24 years (4%) [76].…”
Section: Resultsmentioning
confidence: 99%
“…Data for Mexico and Brazil associated with epidemics were identified for the late 1940s, with about 753 registered cases in Mexico seen for the period 1945–1949 [23] and a serogroup A epidemic from 1945 to 1951 in Sao Paulo, Brazil with incidence rates of 4·6–24·2 cases/100 000 inhabitants [24, 25]. Due to scarcity of more historical data, the following sections focus on the epidemiology from 1970 onwards.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Mexico has remained relatively unaffected since the 1940s and reports very low incidence of disease [23, 26]. SINAVE (Sistema Nacional de Vigilancia Epidemiológica) registered an average of 65 confirmed cases per year between 2003 and 2009 and, based on a total of 60 reported cases in 2006, a national incidence of 0·056 cases/100 000 has been estimated.…”
Section: Introductionmentioning
confidence: 99%